2018
DOI: 10.1007/s00520-018-4443-3
|View full text |Cite
|
Sign up to set email alerts
|

Certainty within uncertainty: a qualitative study of the experience of metastatic melanoma patients undergoing pembrolizumab immunotherapy

Abstract: Despite progress in melanoma patient treatment and outcomes, these patients face sustained uncertainty about their disease trajectory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 29 publications
8
83
0
Order By: Relevance
“…About half of the survivors (53%) reported fear of cancer recurrence and emotional coping difficulties related to the uncertainty of surviving a potentially lethal disease with a novel treatment of which the long-term outcome remained unknown at the time of the start of this experimental treatment. This is consistent with the findings of Levy et al describing the burden of uncertainty in patients on active ICI treatment [ 35 ]. Posttraumatic stress disorder was present in one-third of the survivors and was related to the moment of receiving a diagnosis of incurable cancer, the traumatic course of disease progression, or the occurrence of irAEs.…”
Section: Discussionsupporting
confidence: 93%
“…About half of the survivors (53%) reported fear of cancer recurrence and emotional coping difficulties related to the uncertainty of surviving a potentially lethal disease with a novel treatment of which the long-term outcome remained unknown at the time of the start of this experimental treatment. This is consistent with the findings of Levy et al describing the burden of uncertainty in patients on active ICI treatment [ 35 ]. Posttraumatic stress disorder was present in one-third of the survivors and was related to the moment of receiving a diagnosis of incurable cancer, the traumatic course of disease progression, or the occurrence of irAEs.…”
Section: Discussionsupporting
confidence: 93%
“…It is characterized by ambiguity, complexity, lack of information and unpredictability . A recent study of the lived experiences of patients with metastatic melanoma undergoing checkpoint inhibitor treatment reported that cyclical uncertainty across investigation and treatment episodes characterized their experiences . Findings from the present study extend this knowledge by providing new insight into the experience of uncertainty by bereaved carers.…”
Section: Discussionsupporting
confidence: 64%
“…Such conversations may also reveal unvoiced expectations, such as those shown by the carers in our study, who experienced difficulties reconciling a diagnosis of advanced disease associated with seemingly trivial symptoms, or a possible terminal prognosis when the patient looked healthy and continued to live an active life. That patients with advanced melanoma wish to – and largely can – live ordinary lives has previously been reported, as has a denial of awareness of the seriousness of a patient's disease on the part of family members, in response to an uncertain prognostic trajectory . Clinical practice guidelines recommend an open disclosure policy when discussing prognosis; however, the present study highlights the importance of checking the type of information the patient and/or carer wishes to know and at what level of detail, and addressing the often unspoken expectations of patients and carers, which may be discordant with the information provided by medical specialists.…”
Section: Discussionmentioning
confidence: 71%
“…Adverse events should not just be seen as a direct result of immunotherapy, such as fatigue, colitis, pancreatitis and various others 17 . As Levy et al describe, living with melanoma under immunotherapy could be compared to living in a phase of uncertainty, like playing a Russian roulette 18 . Particularly noteworthy was the fact that all grades of adverse events had an impact on the quality of life of the patient, besides the less common adverse events 19 …”
Section: Discussionmentioning
confidence: 99%